Project from remembering the past toward a positive future: What kind of model of truth abd trust/reconciliation does Serbia need? - Hanak Nataša (Temida)
The Victimology Society of Serbia, with the support of FES (Friedrich Ebert Stiftung) and the Ministry of Culture of Serbia, conducted a project entitled From remembering the past toward a positive future: what kind of model of truth and trust/reconciliation does Serbia need? The project was launched with the aim to secure a broad public discussion at the level of the local communities about the issues of truth and reconciliation and with the final objective to arrive at a model of truth and reconciliation for Serbia. The main part of the project consisted of a series of public discussions, organized in the form of debates in small groups. The debates were recorded and the transcripts were analyzed in detail later. Besides, an informative brochure on truth and reconciliation was printed and handed out with an accompanying questionnaire, and two public appeals were issued to the citizens to send in their ideas and proposals.